2022
DOI: 10.1128/jcm.00421-22
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Tongue Swab Testing Using Xpert MTB-RIF Ultra for Tuberculosis Diagnosis

Abstract: Tongue dorsum swabs have shown promise as alternatives to sputum for detecting Mycobacterium tuberculosis (MTB) in patients with pulmonary tuberculosis (TB). Some of the most encouraging results have come from studies that used manual quantitative PCR (qPCR) to analyze swabs.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
51
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(54 citation statements)
references
References 15 publications
2
51
0
1
Order By: Relevance
“…Both reserved and duplicate samples (total N=18) were paired with manual OSA data. Samples were tested by Xpert Ultra by using either of two methods described elsewhere (22), depending on whether they were reserve or duplicate. Briefly, in one method ("boil method"), 200 µL)halfsamples, which were previously boiled and stored frozen, were thawed and received 2.2 mL TE buffer.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Both reserved and duplicate samples (total N=18) were paired with manual OSA data. Samples were tested by Xpert Ultra by using either of two methods described elsewhere (22), depending on whether they were reserve or duplicate. Briefly, in one method ("boil method"), 200 µL)halfsamples, which were previously boiled and stored frozen, were thawed and received 2.2 mL TE buffer.…”
Section: Methodsmentioning
confidence: 99%
“…Duplicate samples, which were not previously boiled, were processed by the "single swab SR method" described in reference (22). These 0.5-mL samples were thawed at ambient temperature for 30 min, then supplemented with 0.3 mL TE and 1.6 mL of Cepheid Sample Reagent (SR).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using a different sampling technique, oral swab analysis, Wood and colleagues confirmed that TB is indeed present in the oral cavity when they reported that nylon swabs of the tongue and mouth assayed via insertion sequence IS 6110 PCR detected 18 of 20 (90%) South African patients with TB confirmed via the pre-Ultra GeneXpert MTB/RIF assay on sputum ( 7 ). A larger and more recent study from Uganda of oral swab analysis with Xpert Ultra in 183 adults with possible TB showed a slightly lower sensitivity of 78% (95% CI, 64 to 88%) relative to relative to a sputum reference standard and an outstanding specificity of 100% (95% CI, 97 to 100%) ( 8 ). Saliva is also now widely used for molecular diagnosis of COVID-19, where it has high sensitivity, even among patients without symptoms ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] We and others have shown that MTB DNA is deposited on the oral epithelium during active TB, and can be detected by oral swab analysis (OSA). [4][5][6][7][8][9][10][11][12][13][14][15] In OSA, the dorsum of the tongue is brushed with a sterile swab. The swab head with collected material is deposited into a tube for MTB DNA detection by nucleic acid amplification testing (NAAT).…”
Section: Introductionmentioning
confidence: 99%